Pengaruh Pengetahuan Mengenai Isu-Isu Lingkungan (Knowledge About Environmental Issues) dan Intensi Untuk Bertindak (Intention to Act) terhadap Perilaku Bertanggung Jawab Lingkungan (Responsible Environmental Behavior) Siswa - Fibula Purnama; I Made Putrawan; Diana Vivanti Sigit (IJEEM - Indonesian Journal of Environmental Education and Management, 2020)
Environmental issues is the problem that need to be solved by all parties, including students, by developing responsible of environmental issues. Students’ responsible environmental behavior is an output that came from factors that have effects toward it. Some of the effects are knowledge about environmental issues and intention to act. This study aims to determine the effect of knowledge about environmental issues and intention to act toward responsible environmental behavior that student have. This research conducted at SMAN 4 Kota Bekasi on the 1st semester, of 2019/2020 school year. The method of this research was survey method with quantitative-causal approach and path analysis. The sample of this research were 98 student grade X MIPA. The instrument for knowledge about environmental issues is a true-false test, the instrument for intention to act and responsible environmental behavior is opinionary. Realiability coefficients for knowledge about environmental issuess’ instrument is 0,77, for intention to act is 0,87, and for responsible of environmental behavior is 0,83. Based of hypothesis test, there is no direct effect between knowledge about environmental issues toward responsible environmental behavior, and there is direct effect between knowledge about environmental issues toward intention to act and intention to act toward responsible environmental behavior. Based on these results, can be concluded that intention to act is not a suitable mediator variable between knowledge of environmental issues and responsible environmental behavior. Keywords: intention to act, knowledge, path analysis, responsible environmental behavior, student.